2020
DOI: 10.1038/s41467-020-19287-7
|View full text |Cite
|
Sign up to set email alerts
|

MAVS is energized by Mff which senses mitochondrial metabolism via AMPK for acute antiviral immunity

Abstract: Mitochondria are multifunctional organelles that produce energy and are critical for various signaling pathways. Mitochondrial antiviral signaling (MAVS) is a mitochondrial outer membrane protein essential for the anti-RNA viral immune response, which is regulated by mitochondrial dynamics and energetics; however, the molecular link between mitochondrial metabolism and immunity is unclear. Here we show in cultured mammalian cells that MAVS is activated by mitochondrial fission factor (Mff), which senses mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 59 publications
(134 reference statements)
0
17
0
Order By: Relevance
“…The currently ongoing respiratory infections are mostly from RNA viruses such as IAV and SARS‐CoV‐2, which are thought to be sensed by the RNA‐sensing (MDA/RIG‐I) pathway rather than the DNA‐sensing (cGAS/STING) system. However, emerging data have shown that the infectious agents might, through directly or indirectly acting on mitochondria, participate in the STING‐mediated pathway (Hanada et al, 2020). The strength and duration of STING pathway appear to be determined by both cellular intrinsic signals and pathogen‐derived cues converging at the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The currently ongoing respiratory infections are mostly from RNA viruses such as IAV and SARS‐CoV‐2, which are thought to be sensed by the RNA‐sensing (MDA/RIG‐I) pathway rather than the DNA‐sensing (cGAS/STING) system. However, emerging data have shown that the infectious agents might, through directly or indirectly acting on mitochondria, participate in the STING‐mediated pathway (Hanada et al, 2020). The strength and duration of STING pathway appear to be determined by both cellular intrinsic signals and pathogen‐derived cues converging at the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…The CSE-induced impairment in IFN responses and consequent dampened innate immune suppression may be triggered through downregulation of RIG-I, MDA-5 and TLR3 via IKB kinase epsilon (IKBKE)-mediated regulation of interferon regulatory factors (IRFs), as observed by downregulation of RIG-I , MDA-5 , and TLR3 genes upon CSE stimulation. Additionally, CSE-induced attenuation of interferon responses may be triggered by increased levels of mitochondrial antiviral signaling (MAVS) inhibitors such as E3 ligases Trim29, Smurf1/2, March5 that degrade MAVS or by NLRX1-mediated MAVS inhibition [ 37 ]. This NLRX-mediated inhibition of MAVS and downregulation in interferon response is reported to be regulated via the Tu mitochondrial translation elongation factor (TUFM) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-33/33* was found in macrophages infected with vesicular stomatitis virus (VSV) to inhibit MAVS accumulation by targeting AMPK, thereby inhibiting RIG-I signaling ( Liu et al, 2021a ). Other studies have also shown that AMPK decentralizes MAVS distribution in mitochondria and inhibits proinflammatory factors (IFN-β and IL-6; Hanada et al, 2020 ). Therefore, we suggest that AMPK may inhibit MAVS accumulation by regulating HK2 or lactate, but the specific mechanism needs further experimental proof.…”
Section: Glycolysis and Innate Immunitymentioning
confidence: 97%